Delayed Anti‐CD3 Therapy Results in Depletion of Alloreactive T Cells and the Dominance of Foxp3+CD4+ Graft Infiltrating Cells. Issue 7 (10th June 2013) - Goto, R.; You, S.; Zaitsu, M.; Chatenoud, L.; Wood, K. J.
Abstract The engineered Fc‐nonbinding (crystallizable fragment‐nonbinding) CD3 antibody has lower mitogenicity and a precise therapeutic window for disease remission in patients with type 1 diabetes. Before anti‐CD3 can be considered for use in transplantation, the most effective timing of treatment relative to transplantation needs to be elucidated. In this study anti‐CD3F(ab′)2 fragments or saline were administered intravenously for 5 consecutive days (early: d1–3 or delayed: d3–7) to mice transplanted with a cardiac allograft (H2b‐to‐H2k; d0). Survival of allografts was prolonged in mice treated with the early protocol (MST = 48 days), but most were rejected by d100. In contrast, in mice treated with the delayed protocol allografts continued to survive long term. The delayed protocol significantly inhibited donor alloreactivity at d30 as compared to the early protocol. A marked increase in Foxp3+ T cells (50.3 ± 1.6%) infiltrating the allografts in mice treated with the delayed protocol was observed (p < 0.0001 vs. early (24.9 ± 2.1%)) at d10; a finding that was maintained in the accepted cardiac allografts at d100. We conclude that the timing of treatment with anti‐CD3 therapy is critical for inducing long‐term graft survival. Delaying administration effectively inhibits the alloreactivity and promotes the dominance of intragraft Foxp3+ T cells allowing long‐term graft acceptance.